Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1039/c0dt00587h
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the heterometallic Au(i)–M(i) (M = Cu, Ag) clusters containing the dialkyne-derived diphosphines: synthesis, luminescence and theoretical studies

Abstract: The novel heterobimetallic Au(I)-M(I) (M = Cu, Ag) alkynyl-diphosphine clusters were effectively prepared using a family of dialkynyl-based diphosphines, PPh(2)-C(2)-(C(6)H(4))(n)-C(2)-PPh(2) (n = 0-2). These compounds consist of [Au(x)M(y)(C(2)C(6)H(4)R)(2x)](y-x) clusters (x = (n + 2)(n + 3)/2; y = (n + 1)(n + 2)) "wrapped" in gold-diphosphine "belts" (M = Cu, n = 0, R = H (4); n = 1, R = H (6), OMe (8), NMe(2) (9). M = Ag, n = 0, 1, 2, R = H (5, 7, 10). The solid-state structures of 5 and 6 have been determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…A combination of goldmetal bonds, enabled by the relativistic effects of gold, and alkynyl groups attached to a carbene complex, should facilitate the synthesis of oligomeric or supramolecular coinage metal assemblies. 29 Although terminal alkynes can act as bidentate ligands through end-on and side-on coordination, we initially focused on phenyl-protected alkyne substituents, which should allow for side-on coordination of different metals through π-bonding.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of goldmetal bonds, enabled by the relativistic effects of gold, and alkynyl groups attached to a carbene complex, should facilitate the synthesis of oligomeric or supramolecular coinage metal assemblies. 29 Although terminal alkynes can act as bidentate ligands through end-on and side-on coordination, we initially focused on phenyl-protected alkyne substituents, which should allow for side-on coordination of different metals through π-bonding.…”
Section: Introductionmentioning
confidence: 99%
“…[3,8,14] The non-bonding separations are 3.1932(7) and 3.2444(6) in 5 and 6, and exceed the sum of Cu and Au van der Waals radii (3.06 ), pointing to the absence of substantial metal-metal interaction. The nuclearity of the {Au 6 Cu 2 } cluster has been observed in some our previous works on Au I -Cu I alkynyl compounds, [17,21] but the structural arrangement of these novel clusters is unprecedented and has a dramatic influence on the photophysical properties (see the corresponding section below).…”
Section: Resultsmentioning
confidence: 85%
“…Interestingly, in the case of the alkynyl ligands with cyclohexanolyl and isopropanolyl substituents, the clusters [Au 6 Cu 2 A C H T U N G T R E N N U N G (C 2 R) 6 A C H T U N G T R E N N U N G (P^P) 3 ] 2 + (R = C 6 H 11 O (7), C 3 H 7 O (8)), which have the previously reported structural type, [17,20,21] were obtained nearly quantitatively when the higher amounts of the diphosphine were used (Scheme 4).…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, it was shown that the contribution of the phosphine orbitals into emissive electronic states is essentially smaller. Nevertheless, these ligands undoubtedly affect the energy of the electronic transitions and dramatically influence the emission efficiency, varying the quantum yields from 96% to 8% for the structurally similar compounds with Ph 2 PeC 6 H 4 ePPh 2 and Ph 2 PeC^CeC^CePPh 2 diphosphines, respectively [24,25]. In the present work we report on the synthesis, structural characterization and spectroscopic studies of the "rods-in-belt" AueCu complexes based on the Ph 2 Pe (CH 2 ) 4 ePPh 2 ligand with non-rigid aliphatic spacer and comparison of their photophysical characteristics with those obtained for the related compounds containing aromatic spacers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, accessible modification of these ligands provides an opportunity for fine tuning of the physicochemical properties of the resulting organometallic aggregates. Recently we have described a family of the polynuclear AueCu and AueAg complexes, which contain a central core composed of gold(bis-alkynyl) "rods" and copper or silver ions stabilized by the {Auediphosphine} 3 "belt" (diphosphines: Ph 2 Pe(C 6 H 4 ) n ePPh 2 , n ¼ 1e5, Ph 2 PeC^Ce(C 6 H 4 ) n eC^CePPh 2 , n ¼ 0e2) [17,24,25]. Particular attention was paid to the photophysical studies of these compounds, which demonstrate extremely high quantum yields of phosphorescence, negligible quenching of emission with molecular oxygen and intriguing non-linear properties.…”
Section: Introductionmentioning
confidence: 99%